2015
DOI: 10.1364/oe.23.003851
|View full text |Cite
|
Sign up to set email alerts
|

Biaxial crystal α-BaTeMo_2O_9: theory study of large birefringence and wide-band polarized prisms design

Abstract: α-BaTeMo(2)O(9) is a novel biaxial crystal with wide-band transmittance spectrum. The refractive index dispersion curves and birefringence of the α-BaTeMo(2)O(9) crystal were obtained in spectral range of 0.4~5 μm. The origin of the birefringence for the crystal has been calculated and interpreted on the basis of the crystal structure combined with theoretical studies. The polarized directions and formulations of refractive index of optical waves in biaxial α-BaTeMo(2)O(9) were investigated by solving the refr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Our studies show that this novel hybrid metamaterial features a linear birefringence mainly caused by the orthorhombic carbon phase. The linear birefringence remains nearly constant (Δ n = 0.09 ± 0.005) over a spectral range of 400–700 nm, which is generally comparable to naturally birefringent materials, but it outperforms other orthorhombic crystalline structures . Furthermore, the combination of the field enhancement introduced by the plasmonic Au–Ag nanoparticle inclusions and the birefringence suggest a strong potential for opto‐electronics, nanophotonic, nonlinear optical experiments, and applications …”
mentioning
confidence: 89%
“…Our studies show that this novel hybrid metamaterial features a linear birefringence mainly caused by the orthorhombic carbon phase. The linear birefringence remains nearly constant (Δ n = 0.09 ± 0.005) over a spectral range of 400–700 nm, which is generally comparable to naturally birefringent materials, but it outperforms other orthorhombic crystalline structures . Furthermore, the combination of the field enhancement introduced by the plasmonic Au–Ag nanoparticle inclusions and the birefringence suggest a strong potential for opto‐electronics, nanophotonic, nonlinear optical experiments, and applications …”
mentioning
confidence: 89%
“…Noncentrosymmetric polar inorganic oxide materials are promising candidates for second order nonlinear optical applications namely second harmonic generation (SHG). [1][2][3] In the recent years there is potential interest in nding novel materials which can produce visible, ultraviolet and infra-red laser radiation at wavelengths that are presently inaccessible via conventional sources for many industrial, medical, biological and entertainment applications. [4][5][6] Noncentrosymmetric polar inorganic oxides are technologically important for several applications, such as piezoelectricity, nonlinear optical properties, ferroelectricity and pyroelectricity.…”
Section: Introductionmentioning
confidence: 99%
“…1 The newly discovered phase motivated several researchers to investigate the unique properties of this phase. 2,3,14 Recently, Raman spectra using pulsed laser diode pumped Nd:YAG/Cr 4+ :YAG was reported for a-BaTeMo 2 O 9 phase, 14 they found that the high energy output pulse have potential application in medical treatment and laser ranging. 14 Using two continuous wave lasers 808 and 1064 nm as photoinducing sources Majchrowski et al 2 have measured the SHG at the wavelength 1064 nm under photoinducing treatment of monoclinic piezoelectric b-BaTeMo 2 O 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transformation of frequencies within the wide spectral range of electromagnetic radiation (between 1–15 μm) for ultrafast lasers (from picoseconds up to femtoseconds) and large power densities can lead to significant progress in laser engineering. The method used for such frequency transformations is usually the generation of harmonic frequencies by employing high quality NLO crystals possessing large second optical susceptibilities89. In particular, the main method employed for frequency transformation is the second harmonic generation (SHG), where organic and inorganic crystals are now among the best1011.…”
mentioning
confidence: 99%